Implementation of the Indonesian Ministry of Home Affairs Regulation No. 81 of 2015 on the Village and Urban Village Development Evaluation Application (EPDESKEL): A Study of Five Nagari in Lubuk Basung District, Agam Regency, Indonesia - Musfi Yendra; Doddie Arya Kusuma; Wahyudi Wahyudi; Emi Handrina; Eriandi Eriandi; Riswanto Bakhtiar; Serli Serli; Dodi Saftian Alamsyah; Suryaningsih Suryaningsih; Rinawati Rinawati (The Future of Education Journal, 2026)
The Indonesian Ministry of Home Affairs Regulation No. 81 of 2015 on Village and Urban Village Development Evaluation provides a policy framework for assessing the developmental progress of villages and urban villages. The implementation of the Village and Urban Village Development Evaluation Application (EPDESKEL) is expected to optimize local governance by enhancing the effectiveness and efficiency of coordination between local governments and village administrations. This study aimed to examine the implementation of the EPDESKEL application and its contribution to improving the quality of government supervision in five Nagari in Lubuk Basung District, Agam Regency, Indonesia. A qualitative research design with a descriptive approach was employed. The study involved five Nagari in Lubuk Basung District and officials from the Department of Community and Village Empowerment (DPMN) as research participants. Data were collected through in-depth interviews, observations, and document analysis and were analyzed using the Miles and Huberman interactive model. The findings indicate that the implementation of the Indonesian Ministry of Home Affairs Regulation No. 81 of 2015 through the EPDESKEL application has generally been carried out effectively in the Nagari of Lubuk Basung District and has produced positive outcomes for local governance and supervisory practices. Nevertheless, several challenges remain, including limited community participation and awareness regarding population administration, as well as the need for more intensive guidance and supervision from local government authorities. These findings suggest that strengthening institutional support and community engagement is essential for optimizing the implementation of EPDESKEL and achieving more effective village governance.